(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
This experience report deals with the participation of 02 (two) professors and 08 (eight) students from the Federal Rural University of the Amazon – UFRA do Pará, in the 16th Operation carried out by the Extensionist Nucleus Rondon – NER / UDESC, in the west of Santa Catarina. The institutional challenge was accepted in order to understand the application of the Rondon Project developed 10 (years ago) by NER / UDESC, as a powerful tool for University Extension. The Rondon Project developed by NER / UDESC not only provides services to society for its sustainable development, but allows undergraduate students the opportunity to experience their academic theories in the practice of society. All in a non-welfare way, as the exchange of knowledge is a basic principle. There is the strengthening of citizen education for students and the essence of popular education for all, which goes beyond the concept of need. In the future, this Rondon Project methodology may also be applied by UFRA in Pará and Amazônia KEYWORDS: Higher Education. Popular Education. Operation Rondon. Rondon Workshops. Rondon Extensionist Nucleus.